Validation of Morphometric Teaching Materials with South Sumatera Local Fish Content - Madang, Kodri; Destiansari, Elvira; Dewi, Safira Permata (BIOEDUSCIENCE, 2022)
Background: In the local context of South Sumatra, it is known that freshwater fish occupy important sociological and economic aspects. Placement of materials such as examples of belida fish, snakehead fish, betok fish and local species of fish from South Sumatra into the Morphometry course is something that will support the understanding of morphometry. The existence of this material will also meet the demands of the curriculum with contextual material. This study aims to explain the results of construct and material validation on the product of Morphometry subject teaching materials based on local Sumatran content. This research was conducted in the Biology Education Study Program. Methods: This type of research is descriptive qualitative using expert validation sheets. A validation sheet is given and an expert is assessed. Experts who provide assessments include material experts and constructivists. Validation includes aspects of the construct and material on the product of teaching materials.. Results: The validation results show that the results of the construct expert validation obtained 91.42% results and were declared valid/no need to be revised and the material expert validation results obtained 97.14% results and were declared valid/no need to be revised. Conclusions: Based on these results, it can be concluded that the product of teaching materials is declared valid by construct and material experts so that the product can be used for the next process. These results indicate that the teaching materials are in accordance with learning outcomes and can support the learning process of Morphometry Subjects.